Development of real-time navigation system by using pure pursuit guidance for unmanned surface vehicle - Putri Nur Farhanah, Mohd Shamsuddin (2024)
The navigation system was serving as the Unmanned Surface Vehicle (USV) cardinal reference, leveraging GPS receivers and inertial sensors to precisely determine its geographical coordinates and directional orientation. The USV was receiving full support from the navigation system in determining its current and future poses between two points, while its current position was being determined by several sensors for estimating the heading towards the target or the following path. However, the USV encountered difficulty in tracking the target's current position on the water while moving towards it, due to limitations in its programming to navigate based on initial computation commands such as heading and distance. Therefore, a Pure Pursuit algorithm will be developed to assist the USV in tracking the target's position, ensuring that the vehicle will follow the new path information, and enhancing the real-time performance of the USV as it tracks the target's current position based on the output commands. This research aims to create a real-time tracking algorithm for guiding the USV to the target using the Pure Pursuit method, and to test how well it reduces sideways errors and reaches the target. The USV system was equipped with a tracking concept and method involving determining the distance and heading angle between two coordinates (Target and USV). To follow the trajectories of the current path, the Pure Pursuit guidance was implemented in the system. In summary, by 75s, the USV reached the last target position, demonstrating successful navigation along the trajectory path. This success was attributed to the integration of the dead reckoning method with Pure Pursuit guidance, which continuously updated the USV's position and orientation using onboard sensors. The Pure Pursuit algorithm works by focusing on the nearby path relative to the USV's position, guiding it with steering directions based on its current position and orientation. From 40s to 70s, the USV followed the target, reaching its last known position at 75s, showing how the tracking algorithm effectively guides the USV using Pure Pursuit guidance. Pure Pursuit guidance helps the USV stay on track by adjusting its steering to aim towards a target point along the planned path. This reduces sideways errors, which is the distance between the USV and the path. The system constantly adjusts based on sensor feedback, ensuring the USV follows the path closely with minimal errors. It will facilitate adaptation to dynamic targets, ensuring reliable performance in changing conditions and agile maneuvering through careful consideration and suitable mitigation strategies.